Etnografía del pensamiento del profesorado de matemática de Santiago de Cuba - Justis Katt, Osmany; Galán Segura, Camelia Virgen (Universidad de Costa Rica, 2019)
This paper focuses as a problem inadequacies in the quality of student learning in mathematics revealed in the low results of the entrance exams to Higher Education in the province of Santiago de Cuba. The research found no antecedent ethnographic studies in the educational context of Santiago, as a consequence, it is proposed as an objective: to develop an ethnographic approach in regard to the way in which the teachers of mathematics conceive the design of their pedagogical management to produce lasting knowledge in the students. The methodology used supports a qualitative approach, constituting an ethnographic research that used as an essential method for obtaining information the field research in a population of 229 teachers, of which 83 were the sample. This research was carried out from September 2016 to October 2017. The utilization of ethnographic techniques complemented the methodology to achieve as a main outcome a cultural-pedagogical-operative matrix for the educational practice in the teaching of mathematics and, at the same time, revealed theoretical limitations in the understanding of the scope of the pedagogical management of teachers in the acting model in Santiago de Cuba. This result creates the needed methodological conditions for the transfer of good practices in the learning of mathematics supported by ethnography also opens a space for reflection and participation in the way of managing the learning process.